The Effect of Principal Leadership and Work Discipline on Job Satisfaction of Public High School Teachers (International Journal of Education and Literature, 2023)
The purpose of this study was to determine the influence of principal leadership and teacher work discipline on teacher job satisfaction at SMA Negeri in Talang Ubi sub-district. The sample size taken was 57 teachers at SMA Negeri in Talang Ubi sub-district. The sampling technique with purposive sampling is where the respondents taken are some teachers at SMA Negeri in Talang Ubi sub-district. Data collection was carried out by distributing questionnaires that used a 5-point Likert scale to measure 75 statement items. The analysis technique used is multiple linear regression analysis. The results showed that there was an influence of Principal Leadership and Teacher Work Discipline on Job Satisfaction Second, there was an influence of Principal Leadership on Job Satisfaction. Third, there is the influence of Teacher Work Discipline on Job Satisfaction